Effects of the Urease Concentration and Calcium Source on Enzyme-Induced Carbonate Precipitation for Lead Remediation - Wang, Lin; Cheng, Wen-Chieh; Xue, Zhong-Fei; Hu, Wenle (Frontiers in Chemistry, 2022)
The heavy metal contamination during the rapid urbanization process in recent decades has notably impacted our fragile environments and threaten human health. However, traditional remediation approaches are considered time-consuming and costly, and the effect sometimes does not meet the requirements expected. The present study conducted test tube experiments to reproduce the enzyme-induced carbonate precipitation applied to the lead remediation under the effects of urease concentration and calcium source. Further, the speciation and sequence of the carbonate precipitation were simulated using the Visual MINTEQ software package. The results indicated that higher urease concentrations can assure the availability of CO32- during the enzyme-induced carbonate precipitation (EICP) process towards benefiting the carbonate precipitation. The calcium source determines the speciation of carbonate precipitation and subsequently the Pb remediation efficiency. The use of CaO results in the dissolution of Pb(OH)2, and therefore, discharges Pb ions, causing some difficulty in forming the multi-layer structure of carbonate precipitation, and degrading the Pb remediation. The findings of this study are useful in widening the horizon of applications of the enzyme-induced carbonate precipitation technology to heavy metal remediation.